2018
DOI: 10.17159/2413-3051/2018/v29i4a4529
|View full text |Cite
|
Sign up to set email alerts
|

Design and performance evaluation of wood-burning cookstoves for low-income households in South Africa

Abstract: Many cookstove programmes implemented around the world aimed to reduce fuel consumption and pollutant emissions through the dissemination and adoption of improved cookstoves. A study was carried out for the design of wood-burning cookstoves for low-income households in South Africa by employing user-centred design and co-design/cocreation approaches. Six designed variants of the biomass stove were constructed. Water-heating and emissions tests, using black wattle wood, were conducted to evaluate them for therm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 32 publications
0
4
0
Order By: Relevance
“…A cookstove or tsotso stove is a cooking appliance designed for efficient combustion of biomass fuels like wood, charcoal, or crop residues to reduce fuel use, toxic emissions, and safety risks compared to open fires or rudimentary stoves (Marebane, 2021). Cookstoves play a significant role in many households, particularly in developing countries, but their traditional designs can lead to environmental and health issues due to inefficient fuel combustion and indoor air pollution (Makonese & Bradnum, 2018). To address these challenges, energy‐efficient cookstoves have been developed and promoted as sustainable alternatives to traditional stoves, with the potential to reduce fuel consumption, mitigate deforestation, and improve indoor air quality (Mekonnen, 2022; Yayeh et al, 2021).…”
Section: Literature and Hypothesis Developmentmentioning
confidence: 99%
“…A cookstove or tsotso stove is a cooking appliance designed for efficient combustion of biomass fuels like wood, charcoal, or crop residues to reduce fuel use, toxic emissions, and safety risks compared to open fires or rudimentary stoves (Marebane, 2021). Cookstoves play a significant role in many households, particularly in developing countries, but their traditional designs can lead to environmental and health issues due to inefficient fuel combustion and indoor air pollution (Makonese & Bradnum, 2018). To address these challenges, energy‐efficient cookstoves have been developed and promoted as sustainable alternatives to traditional stoves, with the potential to reduce fuel consumption, mitigate deforestation, and improve indoor air quality (Mekonnen, 2022; Yayeh et al, 2021).…”
Section: Literature and Hypothesis Developmentmentioning
confidence: 99%
“…Global companies/multinationals and BOP communities (Dey et al, 2019;London & Hart, 2004;Rashid & Rahman, 2009;Santos et al, 2015;Santos & Laczniak, 2012;Simanis & Milstein, 2012;Williams et al, 2012) Global companies/multinationals, NGOs, and BOP consumers (Brugmann & Prahalad, 2007;Dey et al, 2019;Santos & Laczniak, 2012;Vellema & Wijk, 2015) Large domestic (local) companies and BOP communities London & Hart, 2010;Nayak et al, 2019;Varman & Belk, 2012) Local producers and BOP consumers (De Silva et al, 2019;Knizkov & Arlinghaus, 2019) Micro ventures and NGOs (Facca-Miess & Santos, 2014) BOP communities and key stakeholders (Hernandez-Cazares et al, 2019) Non-profit sector and BOP consumers (Dwivedi, 2015;Howell et al, 2018;Makonese & Bradnum, 2018) Service providers/ manufacturers/marketers (Bharti et al, 2014;Duarte et al, 2019;Goyal & Sergi, 2015) Research has investigated specific actor perspectives involved in co-creation, such as micro ventures (Facca-Miess & Santos, 2014), local producers (De Silva et al, 2019Knizkov & Arlinghaus, 2019), and manufacturers/marketers (Bharti et al, 2014).…”
Section: Sourcesmentioning
confidence: 99%
“…The researchers also numerically analyzed the cook stove to evaluate the cook stove performance (Baldwin, 1987). Makonese & Bradnum (2018) investigated on six designed variants of the biomass stove to reduce the fuel consumption and pollutant emissions. Their work suggested that better performance was shown by the larger hopper stoves regarding thermal & emission criterion.…”
Section: Introductionmentioning
confidence: 99%
“…Their work suggested that better performance was shown by the larger hopper stoves regarding thermal & emission criterion. Their work also showed that stoves with large hoppers consumed more fuel resulting in higher fire power (Makonese & Bradnum 2018). Among all the previous work, only variation in chimney height is reviewed to evaluate the cook stove performance.…”
Section: Introductionmentioning
confidence: 99%